ON THE SPECTRUM OF A FIRST SCHUR COMPLEMENT RELATED WITH A 3X3 OPERATOR MATRIX - Rasulov, Tulkin; Khudayarov, Sanat (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
We consider a 3X3 operator matrix Â (Hamiltonian) associated with the energy operator of a system describing three particles in interaction, without conservation of the number of particles. The first Schur complement corresponding to Â with respect to the certain decomposition of the three-particle cut subspace of Fock space is constructed and its spectrum is studied. Â